MAY 2013 PLACEMENT ADS (The Accounting Review, 2013)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.THE PENNSYLVANIA STATE UNIVERSITY AT ERIE, The Sam and Irene Black School of Business at Penn State Erie, The Behrend College is seeking qualified applicants for a tenure-track position in Accounting starting August 2013. Qualified candidates will be considered for appointment at all academic ranks (Ph.D. or D.B.A. required; ABDs considered at the instructor level). Primary teaching interest in Financial Accounting is preferred, but applicants from other areas of interest will be considered. A record of relevant industry experience and professional certification are desirable. Both high-quality teaching and an active program of scholarship are expected. Please address letter of application with a vita, copies of recent student evaluations, one research writing sample, and three letters of recommendation to: Accounting Search Committee, Penn State Erie, Sam and Irene Black School of Business, Box ACCTG 2013XAAA, 5101 Jordan Road, Erie PA 16563-1400. Penn State is committed to Affirmative Action, Equal Opportunity, and the diversity of its workforce.THE UNIVERSITY OF TENNESSEE, KNOXVILLE, Department of Accounting and Information Management is accepting applications for a full-time, tenure track position to begin August 1, 2013. Candidates should hold a doctoral degree with an emphasis in accounting or expect to complete all degree requirements by his or her starting date. The ideal candidate will have teaching interests in financial accounting and a doctoral seminar in empirical research, and have a research interest in financial accounting with a possible intersection with other research areas such as corporate governance or tax. Candidates for Assistant Professor should demonstrate excellent teaching potential and have an academic background that strongly suggests an ability to establish an ongoing program of substantive research. Candidates for Associate Professor should demonstrate excellent achievement in teaching and have a substantive research record that reflects a significant ongoing research program. Review of applications will begin on immediately and will continue until the position is filled. The Knoxville campus of The University of Tennessee is seeking candidates who have the ability to contribute in meaningful ways to the diversity and intercultural goals of the University. Please send cover letter, vita, and references, preferably by email, to: Kenneth E. Anderson, Search Committee Chair, Department of Accounting and Information Management, CBA, University of Tennessee, Knoxville, Tennessee 37996-0560. Email: kea@utk.edu The University of Tennessee is an EEO/AA/Title VI/Title IX/Section 504/ADA/ADEA institution in the provision of its education and employment programs and services. All qualified applicants will receive equal consideration for employment without regard to race, color, national origin, religion, sex, pregnancy, marital status, sexual orientation, gender identity, age, physical or mental disability, or covered veteran status.COQUILLE VALLEY HOSPITAL is currently seeking a Chief Financial Officer. The ideal candidate is a senior-level healthcare finance professional who can provide both operational and programmatic support to the organization. The CFO supervises the finance function, including general and patient financial services department, and is the chief financial spokesperson for the organization. The CFO reports directly to the CEO and assists on all strategic and tactical matters as they relate to budget management, cost benefit analysis, forecasting needs, and the securing of new funding. Leads and oversees the analysis and reporting for governmental reimbursement programs (e.g., Medicare, Medicaid). Participates in the development of and implementation of financial policy, provides credible financial analyses, and guides decision making to preserve the financial position and performance of the organization. Bachelor's degree in Business Administration, Finance, Accounting, or equivalent combination of education or experience is required. CPA is preferred. Five to seven years of financial experience, with at least three years in a hospital financial leadership management setting required. Apply URL: http://www.cvhospital.org/NORTHEASTERN UNIVERSITY, The D'Amore-McKim School of Business (DMSB) is pleased to invite applications for the Philip R. McDonald Chair at Northeastern University. The Chair was endowed in the memory of former Dean McDonald by his many friends and colleagues. The candidate selected as the Philip R. McDonald Chair will be eligible for appointment to the rank of full, tenured professor. The holder of the Philip R. McDonald Chair is expected to strengthen and increase the visibility of the DMSB and be a thought-leader within the college, university, and academic and business communities. A private institution in Boston with 22,000 students, Northeastern is a nationally recognized research university and a world leader in the integration of work and learning through its signature cooperative educational program. The College of Business Administration, established in 1922, was recently renamed the D'Amore-McKim School of Business, following a generous gift from two alumni. The DMSB has witnessed a rapid acceleration in the quality of faculty and students as well as in the ranking of graduate and undergraduate programs and faculty research productivity. The Phillip R. McDonald Chair offers a competitive salary, a research fund, summer support, and a reduced teaching load. Interested applicants should send a vita, names of three professional references, and a personal statement of interest to: https://neu.peopleadmin.com/postings/22713ROBERT MORRIS UNIVERSITY invites applications for Assistant/Associate Professor Accounting faculty for the upcoming 2013–2014 academic year. Candidates should have a Ph.D. in Accounting from an AACSB-accredited institution, or be nearing the completion of such program. Candidates must demonstrate the potential for teaching excellence and research productivity. Located in suburban Pittsburgh, Pennsylvania, RMU is a private university with an enrollment of 5,000 students. The RMU School of Business (SBUS) is accredited by AACSB International. Applications should include a letter of application, curriculum vita, teaching evaluations, and evidence of scholarship, copies of official transcripts, and a list of three academic and/or professional references. Submit applications to: Business@rmu.edu c/o Carol MacPhail, Interim Head, Department of Accounting and Taxation. For information, please contact Carol MacPhail at (412) 397-6242 or macphail@rmu.edu or visit http://www.rmu.edu. At RMU, we believe that institutional equity reflects our continued commitment to a community where everyone is both valued and respected. EOESAINT MARY'S UNIVERSITY, The Department of Accounting in the Sobey School of Business at Saint Mary's University invites applications for one tenure-track position. The successful applicant will have strong teaching and research credentials, with an earned doctorate in hand or nearing completion at the time of appointment. A professional accounting designation is also highly desirable. A commitment to research excellence and the ability to teach in either the area of Financial Accounting or Management Information Systems is expected to be important considerations in the appointment. Applicants should submit a letter of application, curriculum vitae, a sample of recent scholarly writing, and the names and full contact information of three referees to: Dr. Jeffrey Power, Co-Chair Department of Accounting, Sobey School of Business, Saint Mary's University, Halifax, N.S. B3H 3C3; Fax: (902) 420-5011 or by email to jeff.power@smu.ca. More information about Saint Mary's University and the Sobey School of Business may be found at http://www.smu.ca and http://www.smu.ca/academic/sobey. . Canadians and permanent residents will be given priority. Saint Mary's University is committed to the principles of employment equity.MONTANA STATE UNIVERSITY, Accounting Option of the College of Business (an AACSB-accredited program) invites applications for a tenure-track faculty position. Candidates are required to hold or be near completion of an earned doctorate in accounting or in business administration with a major in accounting from an AACSB-accredited program. The position requires high-quality teaching and service, and continuing research activity, including publications in respected peer-reviewed journals. Candidates with teaching interests in tax, governmental accounting, accounting information systems, managerial accounting, and financial accounting will be considered. The course load is 6–9 credit hours per semester. Qualified applicants should view the complete position description at http://www.montana.edu/jobs/faculty/13-202 for information on how to apply. Review of applications will begin February 20, 2013. ADA/AA/EO/Vet Pref. Employer.EDINBORO UNIVERSITY OF PENNSYLVANIA is seeking applicants to teach principles of accounting, managerial accounting, and upper-level courses in accounting based on the needs of the department and the qualifications of the candidate. Ph.D. required; ABD will be considered if reasonable expectation of receiving the degree before 8/24/2013. Fluency in the English language for final candidates will be assessed. Offers of employment are contingent upon successful completion of a criminal background check and credential verification. Apply at: https://jobs@edinboro.edu/postings/338RUTGERS, THE STATE UNIVERSITY OF NEW JERSEY, Rutgers Business School Newark and New Brunswick invites applications for a one-year, non-tenure track position at the Assistant Professor level in the department of Accounting and Information Systems. Job Qualifications: A strong commitment to excellence in high-quality innovative research in governmental accounting and auditing; A Ph.D. degree from an AACSB-accredited school in the field of accounting and information systems. Candidates who are close to completion of their degree will also be considered. Teaching load and salary are competitive with research universities. Application Procedure: The review of applications will begin immediately and applications will be accepted until the position is filled. Apply electronically by sending your application via email to: Professor Miklos Vasarhelyi, Search Committee Chair at: miklosv@andromeda.rutgers.edu. Only electronic submissions will be accepted. Please attach the following documents with your electronic submission: application letter, vita, and job market paper. Finalists will be asked to forward official transcripts, three letters of reference, and other supportive materials as requested by the Search Committee. Rutgers University is an Affirmative Action/Equal Opportunity Employer. Women, members of minority groups, and persons with disabilities are encouraged to apply.OKLAHOMA STATE UNIVERSITY, School of Accounting, The School of Accounting at Oklahoma State University invites applications for a position beginning in fall of 2013 at the clinical assistant, associate, or full professor level. All applicants must have a commitment to instructional excellence. All areas of research and teaching will be considered. The clinical position is primarily a teaching position although some research is required to maintain AACSB accreditation standards. Applicants must have an appropriate earned doctorate and have a distinguished ongoing record of scholarship. The position is located on the OSU Tulsa campus. Screening will begin immediately and will continue until the position is filled. Interviews will begin in the Spring 2013 semester. A letter of application, vita, and summary of teaching evaluations should be sent to: Bill Schwartz, School of Accounting, Oklahoma State University, 401 Business Building, Stillwater, OK 74078; Phone: (405) 744-5100; Email: bill.schwartz@okstate.edu. OSU is an Affirmative Action/Equal Opportunity/E-Verify employer committed to diversity. The position is contingent on available funding.OKLAHOMA STATE UNIVERSITY, School of Accounting in the Spears School of Business invites applications for a tenure-track position beginning Fall, 2013 at the Assistant, Associate, or Full Professor level. All areas of research and teaching emphasis will be considered but preference will be given to applicants prepared to teach auditing at the undergraduate and graduate levels. Applicants must have an appropriate earned doctorate in accounting. All applicants must have a commitment to instructional excellence. Applicants at the senior level should have a distinguished ongoing record of research publications and scholarship activities. The position is located on the OSU/Stillwater campus, but could be called upon to occasionally teach on the OSU/Tulsa campus. Applicant screening will begin immediately and will continue until the position is filled. Interviews will begin in the spring, 2013 semester. All positions are contingent upon available funding. A letter of application, curriculum vitae, and a summary of teaching evaluations should be sent to: Robert M. Cornell, Head, School of Accounting, Oklahoma State University, 401 Business Building, Stillwater, OK 74078; Phone: (405) 744-5123; Email: robert.cornell@okstate.edu. Oklahoma State University is an Affirmative Action/Equal Opportunity/E-Verify employer committed to diversity.